Analisis Media Flashcard Terhadap Kemampuan Komunikasi Anak Autis di SLB TNCC Banda Aceh - Sherina Wifda; Afifah Munira; Putri Situmorang; Hijriati Hijriati (Institut Nalanda, 2024)
Children with special needs (ABK) are children who have obstacles in their development caused by internal and external factors. Autism is a congenital disorder that children experience from birth, where it affects the child's ability to communicate or speak, making it difficult for the child to communicate both verbally and non-verbally. Difficulty speaking experienced by autistic children hinders the child from interacting with people in the surrounding environment. Flashcard media is media that contains interesting and simple pictures that can help improve children's speaking skills. The aim of this research is to find out the influence of flashcard media on speaking abilities in autistic children. The type of research used in this research is descriptive qualitative. Data collection techniques in this research are observation, interviews and documentation. The subject in this research was an autistic child with the initials A, a 5 year old male. The research results show that using flashcard media can improve speaking skills in autistic children.